Comparison of interferon γ release assays and conventional screening tests before tumour necrosis factor α blockade in patients with inflammatory arthritis. Issue 01 (28th January 2009) - Martin, J; Walsh, C; Gibbs, A; McDonnell, T; Fearon, U; Keane, J; Codd, M B; Dodd, J; Veale, D; FitzGerald, O; Bresnihan, B
Abstract : Objective: To compare the performance of two interferon γ release assays (IGRAs) and conventional screening tests in patients with inflammatory arthritis undergoing screening for latent tuberculosis infection (LTBI) before treatment with anti-tumour necrosis factor α (anti-TNFα) compounds. Methods: Successive patients were subjected to conventional LTBI screening, including a tuberculin skin test (TST). The T-SPOT.TB test was performed on all patients and the QuantiFERON-TB Gold test was performed on a large subset. The results of the IGRAs were compared with the results of conventional screening tests. Results: A total 150 patients were evaluated. The majority (57.9%) had rheumatoid arthritis. Previous vaccination with Bacille Calmette–Guerin was confirmed in 82% of patients. No patient had received prior anti-TB treatment. A total of 57 patients (38.0%) had at least one positive conventional risk factor. In contrast, an unequivocally positive T-SPOT.TB test was seen in only 14/143 (9.8%). There was 98.2% agreement between the two IGRAs. Statistically significant associations were found between each of the IGRAs and both TST and risk history, but not chest x -ray (CXR). A positive IGRA result was significantly associated with increased age. TB was not reactivated in any patient during the follow-up period. Interpretation: This study suggests that IGRAs may be useful when screening for LTBI before anti-TNFα therapy in patients with immune-mediated inflammatory diseases. The observations reported here also highlight the inadequate performance of CXR as a marker of LTBI.